Formation of hierarchical assemblies by collagen peptides derived from fish skin and bladder and their subsequent application as antiperoxide agents in lipid-rich food. (5th January 2023) - Sumeet, Charitha; Bajaj, Mayur; Kumar, Indresh; Yelleti, Geethika; Asokan, Vishwadeep; Tagadghar, Pawan; Banerjee, Pradipta
Abstract: This study attempts to identify the significant role played by the secondary and tertiary structure of collagen-derived peptides that are involved in lipid peroxide quenching in food products. Fish collagen hydrolysate (CH) was extracted with an efficiency of 70%. The constituent peptides of CH (8.2–9.7 kDa) existed in a polyproline-II (PP-II) conformation and at a minimum concentration of 1 mg ml −1 and pH range 7 to 8, assembled into a stable, hierarchical, quasi-fibrillar (QF) network. The peroxide quenching activity of this QF-CH increased with increasing ionic stability of the assembly and decreased upon proteolytic dismantling. Upon being used as an additive, the QF-CH reduced peroxide formation by 84.5% to 98.9% in both plant and fish-based oil and increased the shelf life of soya oil by a factor of 5 after 6 months of storage. The addition of QF-CH to cultured cells quenched peroxide ions generated in situ and decreased stressor activity by a factor of 12.16 abundant peptides were identified from the CH. The reason behind the high efficacy displayed by CH was attributed to its unique charge distribution, prevalence of proton-donating amino acid residues and proximal charge delocalization by the QF network, making fish derived CH a suitable substitute for antiperoxide agents in lipid-rich food. Graphical Abstract: